The Demand for Labor: An Analysis Using Matched Employer-Employee Data from the German LIAB. Will the High Unskilled Worker Own-Wage Elasticity Please Stand Up? - Addison, John T. (2005)
This paper uses matched employee-employer LIAB data to provide panel estimates of the structure of labor demand in Germany, 1993-2002, distinguishing between highly skilled, skilled, and unskilled labor and between the manufacturing and service sectors. Reflecting current preoccupations, our demand analysis seeks also to accommodate the impact of technology and trade in addition to wages. The bottom-line interests are to provide elasticities of the demand for unskilled (and other) labor that should assist in short-run policy design and to identify the extent of skill biases or otherwise in trade and technology.